Environmental Conflict, Capital as Power . . . and a Nice Trip to London - Adam Marshall (Manchester Metropolitan University, 2023)
In my PhD thesis, which I am currently in the process of writing up, I explore the UK fracking conflict as a means of elucidating its political economic drivers and dynamics. In the process, I hope to also shed light on the political economic drivers of socio-ecological conflict and crises more broadly. To achieve these aims, my research combines a novel theory of capitalism – the capital as power (CasP) approach to political economy – with a unique mix of qualitative and quantitative research methods. While my thesis contributes primarily to debates at the intersection of ecological economics and political ecology, it also aims to extend the frontiers of research on CasP.
Keywords: P00; P18; Q5; 330; capital as power; fracking; energy; sustainability; United Kingdom